(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
ABSTRACTIn the current work, a thermosyphon was used to investigate the effect of condenser length on its performance. Experimentally by using a pipe of copper having same evaporator length of 120 mm and three different condenser lengths which were 400 mm , 500 mm and 600 mm. The internal and external diameters of the thermosyphon were 26 mm and 28 mm respectively. The evaporator part of the thermosyphon was immersed in the electrical transformer oil, which heated by external heater from ambient temperature to approximately 80 oC, while the condenser part was left to cool naturally by air. Five thermocouples were located on the thermosyphon wall to read the temperature distribution at different positions. The working fluid was water with filling ratio of 50%.The results have obviously shown that temperature gradient was decreased when the condenser length increased and giving a better performance for heat dissipation. The percentage of temperature gradient was positively correlated to the condenser length and it was found that condenser length of ( 400 , 500 , 600) mm gave percentage of decreasing temperature gradient are 67.94 % , 72.94 % , and 77.06 % respectively with respect to that without using thermosyphon .